Understanding dietary motivations that affect the performance of collegiate street dance athletes - Cabrera, Danna Carys O. 2000-; Castro, Camille B. MSHMS (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2023)
Dance has significantly affected many people's lives, especially professional dancers. Dancers in general give importance to their skills and physique due to being athlete-performer, making health and nutrition important in improving their performance as the daily food choices of these athletes may affect the aforementioned factors. Consequently, a lot of dancers do not have diet requirements in their team and many of them also do not know what their proper nutrition should be. They choose to follow different diets to achieve specific weight goals that fit into society’s standards. Numerous factors may or may not affect one’s nutritional and dietary motivations. Thus, this study will focus on street dance athletes, specifically, members of a collegiate street dance team which aims to analyze and understand each athlete’s different nutritional and dietary motivations such as their diets and the reasons behind their food choices to assess if requiring nutritional practices and diet is necessary on collegiate street dance athletes in preparation for a competition.
Vita
Thesis ( Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Diet; Athletes -- Nutrition; Motivation -- Psychology; Collegiate athletes